K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

6 tháng 9 2016

(y - 3)(y + 3)(y2 + 9) - (y2 + 2)(y2 - 2) = [ (y - 3)(y + 3) ](y2 + 9) - [ (y2 + 2)(y2 - 2) ]

= (y2 - 9)(y2 + 9) - (y4 - 4) = (y4 - 81) - (y4 - 4)

= y4 - 81 - y4 + 4

= -77

6 tháng 9 2016

(y-3)(y+3)(y2+9)-(y2+2)(y2-2)
=(y2-9)(y2+9)-(y4-4)
=y4-81-y4+4
=-77

7 tháng 9 2016

\(\left(y-3\right)\left(y+3\right)\left(y^2+9\right)-\left(y^2+2\right)\left(y^2-2\right)\)

\(=\left[\left(y-3\right)\left(y+3\right)\right]\left(y^2+9\right)-\left[\left(y^2+2\right)\left(y^2-2\right)\right]\)

\(=\left(y^2-9\right)\left(y^2+9\right)-\left(y^4-4\right)\)

\(=\left(y^4-81\right)-\left(y^4-4\right)\)

\(=y^4-81-y^4+4\)

\(=-81+4\)

\(=-77\)

16 tháng 9 2016

a/ \(x\left(x+4\right)\left(x-4\right)-\left(x^2-1\right)\left(x^2+1\right)=x\left(x^2-16\right)-x^4+1=-x^4+x^3-16x+1\)

b/ \(\left(y-3\right)\left(y+3\right)\left(y^2+9\right)-\left(y^2+2\right)\left(y^2-2\right)=\left(y^2-9\right)\left(y^2+9\right)-y^4+4=y^4-81-y^2+4=-77\)

17 tháng 9 2017

b) \(\left(2x+y\right)\left(4x^2-2xy+y^2\right)-\left(2x-y\right)\left(4x^2+2xy+y^2\right)\)

\(=\left(2x+y\right)\left(4x^2-2xy+y^2\right)+\left(2x+y\right)\left(4x^2+2xy+y^2\right)\)

\(=\left(2x+y\right)\left(4x^2-2xy+y^2+4x^2+2xy+y^2\right)\)

\(=\left(2x+y\right)\left(8x^2+2y^2\right)\)

\(=\left(2x+y\right)\left(4x+y\right).2xy\)

2 tháng 10 2018

Bài 1:

a.\(\left(x+y\right)^2-\left(x-y\right)^2=\left(x+y-x+y\right)\left(x+y+x-y\right)=2\left(x+y\right)\)

b.\(2\left(x+y\right)\left(x-y\right)+\left(x+y\right)^2+\left(x-y\right)^2=\left(x+y+x-y\right)^2=4x^2\)

25 tháng 10 2015

a) (x+y+x_y).(x+y_x+y)

b ) (( x + y )+(x _ y))2

d ) 8x3 + y3 _  8x3 + y=2y3

14 tháng 7 2021

a) (x+3)(x^2-3x+9)-(54+x^3)

= x^3- 3x^2+9x+3x^2-9x+27-54-x63

= -27

b) (2x + y)(4x^2 – 2xy + y^2) – (2x – y)(4x^2+ 2xy + y^2)

= (2x + y)[(2x)^2 – 2x.y + y^2] – (2x – y)[(2x)^2 + 2x.y + y^2]

= [(2x)3^3+ y^3] – [(2x)^3 – y^3]

= (2x)^3 + y^3 – (2x)^3 + y^3

= 2y^3

14 tháng 7 2021

a)(x+3)(X^2-3x+9)-(54+x^3)

\(x^3\)\(3^3 \) - 54 -\(x^3\)

= 27- 54

= -27

b)(2x+y)(4x^2-2xy+y^2)-(2x-y)(4x^2+2xy+y^2)

\((2x)^3\) + \(y^3\)  - [\((2x)^3\) - \(y^3\) ]

\(8x^3\) + \(y^3\) - \(8x^3\) + \(y^3\)

\(2y^3\)

16 tháng 6 2015
  1. a) (2x-y).(4x^2+2xy+y^2)  = 8x3-y3

   b) (x+3).(x^2-3x+9)=x3+33